High Temperature Magnetic Properties of Selected Steel Grades - John W. Wilson; Lei Zhou; Fanfu Wu; Frenk Van Den Berg; Haibing Yang; Claire Davis; Anthony J Peyton (Research and Review Journal of Nondestructive Testing, 2023)
In order to effectively control the microstructure of steel strip during manufacture it is vital that techniques be developed to monitor microstructural changes in the steel at high temperatures. Electromagnetic non-destructive testing is increasingly being used in these applications as it is non-contact, robust, relatively inexpensive and has the potential to provide real-time feedback to control the manufacturing process. However, if the data produced by these systems is to be fully exploited it is necessary to accurately measure the magnetic properties of steel grades of interest at temperatures up to the Curie point. This work details measurements carried out to assess the magnetic properties of selected steels grades, supplied by Tata Steel, up to the Curie temperature using a novel test rig based on a modified Epstein frame designed by the University of Manchester with high temperature trials at the University of Warwick. Several steel grades are studied with the full magnetic hysteresis (BH) loops reported during heating and cooling, along with extracted magnetic parameters including coercivity, magnetic saturation and magnetic permeability. The magnetic parameters of the selected steel grades are compared and implications of the results on electromagnetic monitoring of steel strip during manufacture considered. Results show the developed system has the potential to provide valuable data to inform online electromagnetic monitoring systems.